Sustainable Disclosure Toward Firm Value: Recent Development and Future Research Agenda - Ni Made Sri Rukmiyati; Ida Bagus Anom Purbawangsa; I Gede Kajeng Baskara; Ica Rika Candraningrat (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study aims to investigate empirical research to see the relationship between sustainability disclosure and firm value. This literature review is important for enhancing our understanding of the relationship between sustainability disclosure and firm value. Reviewing prior studies provides valuable insights and conclusions, and identifies trends, patterns, and gaps in the existing research. Articles were identified via publish or perish software and the Web of Science database. Through scanning with PRISMA, we analyzed 43 articles from 24 leading journals from 2007 to 2021. To the best of the researchers’ knowledge, a literature review on the relationship between sustainability disclosure and firm value is unprecedented. This study advances our knowledge of sustainability disclosure as a factor in firm value. In more detail, this study looks at the ideas that have been put out to explain the connection between the two variables and concludes that previous empirical investigations have not produced consistent findings regarding the relationship between sustainability disclosure and firm value. The relationship between sustainability disclosure and firm value has been explored from various theoretical perspectives: legitimacy theory, stakeholder theory, agency theory, signaling theory, and information asymmetry theory.